989 A Retrospective Cohort Study to Assess the Association Between Outdoor Air Quality and Low Birth Weight. (October 2012) - Ribeiro, MC; Llop, E; Branquinho, C; Dias, CM; Tavares, A; Santos, F; Soares, A; Pereira, MJ
Abstract : Introduction: Low birth weight (LBW) is defined by the World Health Organization as weight at birth of less than 2500 g. Epidemiological observations suggest that LBW contributes to a range of poor infant's health outcomes. Other studies suggest that an increase of outdoor air pollution levels may increase the incidence of LBW. This article presents results from a semi-ecological analysis of association between outdoor air quality and LBW in a cohort of mothers participating in Gestão Integrada Saúde e Ambiente (GISA) project, in Alentejo Litoral region (Portugal). Materials: Individual data on birth weight, residence, demographic, social and clinical covariates were collected by questionnaire from mothers (n=1393) participating on GISA project. Air quality data was collected with a lichen diversity biomonitoring program measured at spatiality distributed sampling sites (n=84). Methods: Lichen biomonitoring was used to derive a continuous metric of outdoor air quality exposure. Geostatistical simulation was applied to lichen diversity data to derive equally probable maps of air quality with different exposure scenarios for each pregnant, to gain insight into exposure distribution and exposure uncertainty. Generalized linear models were used to predict the odds of LBW. Results: Factors found significantly (p<0.05) associated to LBW: smoking habits, prenatal surveillance, body mass index, intrauterine growth, weight gain during pregnancy, previous LBW. Air quality was not associated to LBW (odds, 1.001; confidence interval 95%, 0.998–1.006). Conclusions: Air quality was not associated to LBW. Factors found to be significantly associated with LBW are in line with scientific knowledge.